Global food crises: Monitoring and assessing impact to inform policy responses - Benson, Todd; Minot, Nicholas; Pender, John L.; Robles, Miguel; von Braun, Joachim (International Food Policy Research Institute, 2008)
Strong upward trends and increased variability in global food prices over the past two years have led to concern that hunger and poverty will increase across the world. At the same time, rising food prices provide an incentive and opportunity for many developing countries to strengthen the contribution their farmers make to national economic growth and poverty reduction. Policymakers and opinion leaders in developing countries, however, often lack sufficient information to gauge the likely effects of global food crises on their country and to identify, design, and implement policy actions that can best avoid risks and take advantage of opportunities.The deficiencies in information and analysis can lead to over- and underreactions, resulting in policy and market failures. Experiences across countries in 2007 and 2008 show ample evidence of such outcomes. This report seeks to support national decisionmakers, as well as their international development partners, in acquiring information and applying methods for understanding the likely effects of a global food crisis on their country and acting to alleviate the risks and exploit the opportunities brought about by such crises. It describes data and methods and suggests how to facilitate their collection and use. The report then outlines the design and implementation of an open Internet-based portal for sharing reliable, appropriate information and decision-support tools for national policymakers so they can respond quickly to changes in world food markets in an informed manner.